PENGARUH PENGGUNAAN BAHASA SUNDA TERHADAP PENGGUNAAN BAHASA INDONESIA PADA MASYARAKAT KAMPUNG BALANDONGAN KABUPATEN BANDUNG BARAT - Egi Nugraha; Wawan Wawan; Diena San Fauziya (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
The aim of this research is to study the use of Bahasa Indonesia in Kampung Balandongan, Bandung Barat. The research method used is descriptive qualitative with the sociolinguistic approach. The data is collected by using see ably and in-depth observational techniques. The sociolinguistic study is done by considering aspects of speech, which are a speaker, addressee, topic, and location. The result of this research shows that there are several people in Kampung Balandongan who use Bahasa Indonesia and there is code mixing in using Bahasa Indonesia. The language which frequently appears is Sundanese since it is still used and developed by some speaker in that place. In using Bahasa Indonesia, the people should know and understand how to use it in a correct way, whether it is in a formal or informal situation, thus there will be no variation in using language in interaction and communication context.